Experimental investigation of flow through convergent nozzle and the influence of micro jets on the enlarged duct flow field - Ashfaq, Syed; Khan, Sher Afghan (International Publisher for Advanced Scientific Journals (IPASJ), 2014)
Airflow from convergent axi-symmetric nozzle expanded suddenly into circular duct of larger cross-sectional area than that of nozzle exit area were studied experimentally, focusing attention on the wall pressure and the flow development in the enlarged duct. The flow parameters considered in this investigation are the Mach number at the nozzle exit and the nozzle pressure ratio. The geometrical parameters considered are the area ratio between the sudden expansion duct cross-section and the nozzle exit area and the length-to-diameter ratio of the duct. In the present study micro jets were used to investigate the effect of micro jets on the flow field in the suddenly expanded duct. An active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The Mach numbers of the present studies were M = 0.9, 0.8, and 0.6 and the area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied was 4.84. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. From the results, it is seen that the flow in the base region is dominated by the waves, it is proved that the correctly expanded flow is dominated by waves; also, it is found that for L/D in the range L/D = 10 and 8 the flow remains oscillatory mostly for all the Mach numbers. However, these oscillations are suppressed gradually either with the decrease in the L/D ratio in the range 3 to 6 or with decrease in the level of inertia level.